EVALUASI PENERAPAN PROSEDUR AUDIT ATAS BEBAN UMUM DAN ADMINISTRASI DALAM MENDETEKSI KESALAHAN PENCATATAN OLEH KAP ABC - Fiofellisya, Azah Navalatifana; Kirana, Nanda Wahyu Indah (Program Studi Akuntansi Universitas Flores, 2026)
The charging of management's personal expenses to the general and administrative expense account and the practice of ta x avoidance are indications of irregularities that have an impact on the fairness of the presentation of financial statements. This deviation reflects the weak effectiveness of audit procedures in identifying misstatements, especially in accounts that are routine and tend to be less supervised. This study aims to evaluate the effectiveness of the application of audit procedures by the ABC Public Accounting Firm (KAP) on general and administrative expense accounts. This research uses a descriptive qualitative approach with a case study method, which is carried out through observation, documentation, and interviews during the internship period at KAP ABC. The results showed that KAP ABC has implemented audit procedures according to standards, such as vouching, tracing, and cut-off analysis, which are quite effective in detecting potential misstatements. However, audit effectiveness is still affected by document delays and weak client internal controls.